Exploring nanocellulose frontiers: a comprehensive review of its extraction, properties, and pioneering applications in the automotive and biomedical industries - Yusuf, J.; Sapuan, S.M.; Ahmad Ansari, Mubashshir; Siddiqui, Vasi Uddin; Jamal, Tarique; Ilyas, R.A.; Hassan, M.R. (Elsevier, 2024)
Material is an inseparable entity for humans to serve different purposes. However, synthetic polymers represent a major category of anthropogenic pollutants with detrimental impacts on natural ecosystems. This escalating environmental issue is characterized by the accumulation of non-biodegradable plastic materials, which pose serious threats to the health of our planet's ecosystem. Cellulose is becoming a focal point for many researchers due to its high availability. It has been used to serve various purposes. Recent scientific advancements have unveiled innovative prospects for the utilization of nanocellulose within the area of advanced science. This comprehensive review investigates deeply into the field of nanocellulose, explaining the methodologies employed in separating nanocellulose from cellulose. It also explains upon two intricately examined applications that emphasize the pivotal role of nanocellulose in nanocomposites. The initial instance pertains to the automotive sector, encompassing cutting-edge applications in electric vehicle (EV) batteries, while the second exemplifies the use of nanocellulose in the field of biomedical applications like otorhinolaryngology, ophthalmology, and wound dressing. This review aims to provide comprehensive information starting from the definitions, identifying the sources of the nanocellulose and its extraction, and ending with the recent applications in the emerging field such as energy storage and biomedical applications.